2017
DOI: 10.1021/acs.est.6b05005
|View full text |Cite
|
Sign up to set email alerts
|

National Estimate of Per- and Polyfluoroalkyl Substance (PFAS) Release to U.S. Municipal Landfill Leachate

Abstract: Landfills are the final stage in the life cycle of many products containing per- and polyfluoroalkyl substances (PFASs) and their presence has been reported in landfill leachate. The concentrations of 70 PFASs in 95 samples of leachate were measured in a survey of U.S. landfills of varying climates and waste ages. National release of PFASs was estimated by coupling measured concentrations for the 19 PFASs where more than 50% of samples had quantifiable concentrations, with climate-specific estimates of annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(172 citation statements)
references
References 24 publications
8
154
0
Order By: Relevance
“…In the case of landfilling, the PFAS desorption potential from spent GAC needs to be studied. Landfill leachate is one vector through which PFASs are reintroduced into the environment (e.g., Lang et al ) if landfill leachate is shipped to wastewater treatment plants or is aerosolized. Incineration of spent GAC would have to be conducted at temperatures that are sufficiently high to mineralize PFASs.…”
Section: Effectiveness Of Drinking Water Treatment Processes For the mentioning
confidence: 99%
“…In the case of landfilling, the PFAS desorption potential from spent GAC needs to be studied. Landfill leachate is one vector through which PFASs are reintroduced into the environment (e.g., Lang et al ) if landfill leachate is shipped to wastewater treatment plants or is aerosolized. Incineration of spent GAC would have to be conducted at temperatures that are sufficiently high to mineralize PFASs.…”
Section: Effectiveness Of Drinking Water Treatment Processes For the mentioning
confidence: 99%
“…In Table 2, leachate concentrations from the literature are compiled, in which it was possible for us to calculate the shortchain and long-chain concentrations and ratios in a manner similar to this study, because similar PFASs were analysed and the raw data was available. General caveats however with such comparisons are that the analysis methods can differ, PFASs analysed can differ, as can the type of leachate sampled (raw, diluted, treated), as indicated in Table 2, thus preventing exact comparisons, Eggen et al 19 using non-target analysis ( Table 2) reported relatively high X 16 PFAS concentrations of 6123 ng L À1 for raw leachate in Norwegian landlls sampled in 2006 (which in comparison is higher than all landlls in this study except landll VI), and a short-to long-chain ratio of 0.16; thus, indicating that short-chain PFASs have become more dominant in 1972 | Environ. Sci.…”
Section: Leachate Concentrationsmentioning
confidence: 99%
“…To extrapolate these results to the national level, which introduces new uncertainties, a previous report on leachate emissions in Norway concluded that a total volume of up to 1.0 Â 10 7 m 3 is emitted from Norwegian landlls, with 55% of emissions being sent to wastewater treatment plants (WTP) and 45% to the environment. 30 Based on the mean concentrations provided in Table 1 National estimates have also been presented for other countries, such as China, 22 Germany, 17 and the U.S. 16 These were derived by multiplying average emission rates for landlls included in their study by the number of landlls in the country, rather than based on leachate volumes as here. (Table S2 †) and the concentrations in Table 1) of long-chain and short-chain perfluorinated sulfonates (PFSAs) and perfluoroalkyl carboxylic acids (PFCAs) for the Norwegian landfills in this study (Table S7 † Compared to total per capita emission factors from all sources of PFAS, not just landlls, based on river and water treatment plant data in the literature, the contributions of landlls are relatively low.…”
Section: Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to accepting PFAS-contaminated soils, landfills receive several other PFAScontaining commercial products that are discarded at the end of their functional life (Benskin et al 2012). As a result, unlined landfills can act as a source of PFAS-release to groundwater (Lang et al 2017). The resistance of FeG-and RemB-sorbed PFOA to desorption in such conditions suggests that the risk of diffusive transport of PFOA from landfills through leachates into the groundwater will be minimised, which makes these adsorbents highly favourable.…”
Section: Batch Sorption Studiesmentioning
confidence: 99%